FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN REAKSI NYERI AKIBAT TINDAKAN INVASIF PADA ANAK YANG DIRAWAT - Metha Kemala Rahayu, Fajar Tri Waluyanti,Happy Hayati (Institut Kesehatan Hermina, 2019)
Invasive treatments to the children during the period of hospitalization cause pain reactions. The nurses need to know the factors related to pain reactions. The study aims to identify the factors related with pain reactions related to invasive treatments. The design of this study is observational research with cross sectional approach by using non probability sampling method through consecutive sampling with the amount of 90 children respondents. Multivariate data analysis use multinomial regression statistic test. The result of the analysis indicated that there was a significant relationship between fear and pain reaction (p value = 0,018). The emergence of pain reaction “avoidance” from the children who are in fear is as much 5 times greater than children who are not in fear. Nurses need to conduct nursing interventions that can reduce fear in the children behavior in order to minimize pain reaction in form of avoidance.